2013
DOI: 10.1530/rep-12-0439
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of multiple imprinted genes in embryos of tamoxifen-treated male rats

Abstract: Genomic imprinting is an epigenetic phenomenon known to regulate fetal growth and development. Studies from our laboratory have demonstrated that treatment of adult male rats with tamoxifen increased postimplantation loss around mid gestation. Further studies demonstrated the aberrant expression of transcripts of several imprinted genes in the resorbing embryos at days 11 and 13 of gestation including IGF2. In addition, decreased methylation at the Igf2-H19 imprint control region was observed in spermatozoa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…DNA methylation is an important epigenetic regulation influencing chromatin structure, DNA conformation, chromatin stability and the interaction between DNA and protein, which regulates gene expression and thus affects protein function (Jones, ; Kedia‐Mokashi, Kadam, Ankolkar, Dumasia, & Balasinor, ). Recently, research has focused on the relationship between DNA methylation and interspecific crosses leading to reproductive isolation, the generation of species and heterosis (Brown, Piccuillo, & O' Neill, ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is an important epigenetic regulation influencing chromatin structure, DNA conformation, chromatin stability and the interaction between DNA and protein, which regulates gene expression and thus affects protein function (Jones, ; Kedia‐Mokashi, Kadam, Ankolkar, Dumasia, & Balasinor, ). Recently, research has focused on the relationship between DNA methylation and interspecific crosses leading to reproductive isolation, the generation of species and heterosis (Brown, Piccuillo, & O' Neill, ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, injection of testosterone into female mice at birth induces male-associated methylation patterns in the bed nucleus of the stria terminalis (18). Fluctuations in estradiol levels and exposure to estradiol-imitating compounds like Bisphenol A (BPA) have also been linked to DNA methylation changes (19-21). The speed of these methylation changes suggests that sex hormones may interact directly with biological pathways responsible for creating and maintaining methylation marks (for a review, see (22)).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes have been confirmed in humans, with levels of DNA methylation reported to be raised in children conceived by intracytoplasmic sperm injection (ICSI) and also implicated in fetal alcohol spectrum disorders . Further to this, animal studies have shown a decrease in genomic methylation levels in epididymal sperm following chronic exposure to 5‐azacytidine, (a drug that alters DNA methylation), cyclophosphamide and tamoxifen . Despite these theoretical concerns, there is no human data supporting the premise that paternal exposure before or during pregnancy can increase the risk of birth defects or other adverse pregnancy outcomes (apart from infertility as outlined above).…”
Section: Discussionmentioning
confidence: 99%